Power discourses, social development and editorial cartoons: a Botswanan case study. - Sehuhula, Kesalopa (My University, 2019)
Botswana is considered to be one of the better welfare states, though it has selective social development, and a close connection between the economic and political elite, offering potential power conflict. However freedom of expression for political and social critique are said to be under threat in Botswana. The research focuses on the period from 2008 to 2018 when the president of Botswana was Lieutenant General Sir Seretse Khama Ian Khama. It is also a period in which Botswana is seen (by the outside world) as a model for democracy in Africa and is characterised by many changes. Commentary on and critique of these changes often occur in editorial cartoons. The primary aim of the study was to construct a possible analytical model for editorial cartoons, and then to analyse and justify a selected number of editorial cartoons from Botswanan newspapers that make commentary on emerging issues around Botswanan social and economic development. The study develops an analytical system which is applied to interpret the choices made in the cartoons. To accomplish this, the study first provides an exposition of Scott’s theory of hidden transcripts (1990; Munro 1997). Specifically, the project presents Scott’s notions of onstage and offstage discourses, suggesting that the cartoon is a method of entering the concerns of the powerless into the onstage discourse where powerholder and powerless meet. Having set the power model of analysis, the dissertation demonstrates how power relations manifested in the history of social and economic development in Botswana. It then presents important approaches that are instrumental in the creation of editorial cartoons such as historical/contextual events, cartoon theory, metaphor, metonymy and satire. Using these theoretical frames the interrogates what analytical and creative dynamics can be used to inform a visual system, such as editorial cartoons, that comments on cotradictions between social and economic development claims/promises and actions, as they manifest in a particular country. The dissertation therefore presents Scott’s theory and related theories on power. It then outlines the dynamics of social and economic development as a construct, and the role of editorial cartoons as modes of critique. By triangulating these dynamics, the project then analyses selected Botswanan editorial cartoons using this triangulated model in search of meaning, and therefore, by extension, the efficacy of the model. The research found that, by using Scott’s concepts of onstage and offstage discourses to outline the power dimensions evident in social development issues in Botswana, editorial cartoons that engage with potential cotraditions in the political space can be effectively analysed, and therefore, extention be used effectively by editorial cartoonists.
M. Tech. (Department of Fine Art, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Power; Editorial cartoons; Dissertations, Academic.; Editorial cartoons.; Editorial cartoons -- Botswana.